Exploring Islamic School Leadership in a Challenging Southern Thailand Context - Raihani, Raihani (Studia Islamika, 2017)
This study explores leadership practices in different Islamic schools in Southern Thailand, an area where already for decades an ethno-political conflict has been ongoing between Malay Muslims and the Thai Buddhist government. Using a multiple-case study approach, this research selected three Islamic schools one each in the provinces of Pattani, Narathiwat and Yala selecting their principals, teachers, and students as informants. The findings suggest that the principals, in their planning activities, tend to think strategically for the benefit of their schools, their students, and the community at large, that they are willing to compromise with the government so long as not contradicting their religious beliefs and principles, and that they have a strong vision for the school improvement. Under difficult conditions, they always consider the need to establish immediate and more extensive cooperation with various stakeholders to help further improve the school conditions and their output.DOI: 10.15408/sdi.v24i2.4608